Optimal, near-optimal, and robust epidemic control - Dylan H. Morris (Nature Portfolio, 2021)
The COVID-19 pandemic has demonstrated the need for non-pharmaceutical epidemic mitigation strategies that can be effective even if they are limited in duration. Here, the authors derive analytically optimal and near-optimal time-limited strategies for limiting the epidemic peak in the Susceptible-Infectious-Recovered model and show that, due to the sensitivity of such strategies to implementation errors, timely action is fundamental to non-pharmaceutical disease control.